Discourse in curriculum: A focus on film, television, and media studies - Firdaus Noor; Nuril Ashivah Misbah; Dede Suprayitno; Putrawan Yuliandri (Inovasi Kurikulum, 2024)
This article using discourse theory, popularized by Foucault, is used to examine the production and use of knowledge and practices relevant to the discourse that applies to the film, television, and media studies study program curriculum. This research uses the interpretive phenomenology method (Interpretative Phenomenological Analysis), and the classification and framing of data are carried out through focused group discussions. The purposeful sampling technique was chosen through a maximum variation sampling strategy involving eight research subjects to understand the various experiences of campuses that already have similar programs and are considered the most "oriented" stakeholders. The result is that the curriculum discourse produces four themes: scientific vision and mission, graduate profile, learning outcomes, and curriculum structure. In the experience model, participants express discourse themes with actual social reality. In the end, how discourse speaks is expected to be a critical dimension in forming the Film, Television, and Media Studies program curriculum.    Abstrak Artikel ini menggunakan teori Diskursus yang dipopulerkan oleh Foucault digunakan dengan tujuan untuk melihat produksi dan penggunaan pengetahuan dan praktiknya yang relevansinya dengan wacana yang berlaku untuk kurikulum prodi kajian film, televisi, dan media. Penelitian ini menggunakan metode fenomenologi interpretatif (Interpretative Phenomenological Analysis), klasifikasi dan pembingkaian data dilakukan melalui kegiatan diskusi terpumpun/Focus Group Discussion. Teknik purposeful sampling dipilih melalui strategi maximal variation sampling dengan melibatkan delapan subjek penelitian untuk memahami beragam pengalaman dari kampus-kampus yang sudah memiliki program serupa dan dianggap paling "berorientasi" sebagai pemangku kepentingan. Hasilnya bahwa diskursus kurikulum menghasilkan empat tema yaitu visi misi keilmuan, profil lulusan, capaian pembelajaran, dan struktur kurikulum. Model pengalaman, partisipan mengungkapkan tema wacana dengan realitas sosial yang sesungguhnya. Pada akhirnya cara diskursus berbicara diharapkan menjadi dimensi kunci dalam pembentukan kurikulum pada program studi Kajian Film, Televisi, dan Media. Kata Kunci: Diskursus kurikulum; fenomenologi interpretatif; foucault; kajian film, televisi, dan media